Fortune's dream house - Crespo, Nina, 1967- (Harlequin special edition, 2023)
They're practically strangers. But for Max Fortune Maloney to get his house bid accepted, he has to convince his agent, Eliza Henry, to pretend they're wildly in love and heading for the altar. Eliza needs the deal to advance her career, but she fears jeopardizing her reputation almost as much as she fears falling for the sweet-talking cowboy. Her heart, she warns him, is not for sale!